A (FORENSIC) STYLISTIC ANALYSIS OF ADVERBIALS OF ATTITUDE AND EMPHASIS IN SUPREME COURT DECISIONS IN PHILIPPINE ENGLISH - Hernandez, Hjalmar Punla (Indonesian Journal of Applied Linguistics, 2017)
Contemporarily, stylistics today has developed into its multiplicity – one of which is forensic stylistics. Being a powerfully legal written discourse, Supreme Court decisions are a rich corpus in which linguistic vis-a-vis stylistic choices of Court justices could be examined. This study is a humble attempt at stylistically analyzing Supreme Court decisions in Philippine English (PhE) drafted by two Filipino justices. Specifically, it sought to investigate on the classes, placements, and environments of adverbials of attitude and emphasis employed by the two justices, and drew their implications to teaching and learning English for Legal Purposes (ELP). Using McMenamin (2012), Quirk, Greenbaum, Leech, and Svartvik (1985), and Dita’s (2011) frameworks, 54 randomly selected Supreme Court decisions as primary sources of legal language were analyzed. Results are the following. Firstly, the classes of adverbials of attitude in Supreme Court decisions in PhE used by the two judges were the evaluation to the subject of the clause, judgment to the whole clause, and evaluation to an action performed by the subject of the clause, while those adverbials of emphasis were adverbials of conviction and doubt. Secondly, both adverbials they used have placements that were frequently medial and less initial in sentences where they belonged. Thirdly, the two justices put their adverbials within two principal environments, i.e. within functor, and before/after the verb among others. In these regards, legal and stylistic explanations with respect to these recurrent linguistic features in the two justices’ Court decisions were revealed. Implications of the study to ELP are explained. Lastly, trajectories for future (forensic) stylistic analyses have been recommended.